O'Reilly software architecture conference 2016, London, United Kingdom. - Richards, Mark; Laycock, Rachel; Shum, Cassandra; Thompson, Martin; Henney, Kevlin; Kua, Patrick; Harrop, Rob; Safari eBooks; O'Reilly Software Architecture Conference (2016 : London, United Kingdom) ([Place of publication not identified] : O'Reilly Media, 2016)
Includes keynotes from the conference.
The evolution of software architecture / Mark Richards -- Microservices : pros and cons / Rachel Laycock & Cassandra Shum -- Listening to the design pressures / Martin Thompson -- The architecture of uncertainty / Kevlin Henney -- High-performance teams / Patrick Kua -- Am I only streaming? Thinking reactive / Rob Harrop.
Presenters, Mark Richards, Rachel Laycock, Cassandra Shum, Martin Thompson, Kevlin Henney, Patrick Kua, Rob Harrop.
Title and publication information from resource description page (Safari, viewed November 4, 2016).
Keywords: Software architecture; Electronic books